Well before Pinzón: Language expansions and the regional network in the mouth of the Amazon River - Barreto, Bruno de Souza (2025)
At the time of the European invasion, some parts of the Amazon exhibited plural, multiethnic, and multilingual societal formations. Although distinct gradients in population density and political structure existed in different Amazonian settings, archaeological research has shown that some macro-scale patterns are also clearly visible. The transition to AD 1000 is coupled with significant socio-political changes across the Amazon. Such a process is attested by the increased cultural diversity, regional-like patterns of societal integration, and conflict evidence observable in the archaeological record. The transition to AD 1000 is coupled with significant socio-political changes across the Amazon. Such a process is evidenced by increased cultural diversity, conflicts, and regional-like patterns of societal integration, which are observable in the archaeological record. In the lower Amazon, the archaeological data also suggest these shifts are partially related to the demographic growth in the last centuries before the European invasion. In the Amap a State, a region connecting the Guiana Shield to the lower Amazon and its mouth, the shifts are evident through the diversity of ceramic styles, modes of deposition, construction of megalithic ceremonial centres, and other forms of monumental engineering. These changes seem to result from two interrelated phenomena: 1) Population expansions or migrations revealed by phylogenetic patterns associated with the dissemination of large language families and 2) the strengthening of interaction networks during the last centuries before the European arrival certainly provoked ethnogenetic processes through assimilation, intermarriage, war, trade, and borrowings. Through the employment of GIS analysis, computational modelling (of radiocarbon date and other data), ceramic analysis, settlement spatial patterns, and archaeometry, this research aims to evaluate the meanings of the cultural diversity observed in the archaeological record of the late ceramic age in Amap a. As a pivotal point of such a phenomenon, it is aimed to assess the role of language expansions and exchange networks over its formation. The main question is whether such processes led to the birth of a regional network system at the mouth of the Amazon River.